Country-Of-Origin and Perceived Product Quality: Comparison between Chinese and British consumers - xia, dan (2007)
When consumers come across same products manufactured in different countries, they must make a purchasing decision taking into account of different factors. Their decision to purchase a particular product originating from a specific country may be influenced by the fame that country enjoys with producing particular products or by the reputation the specific brand name enjoys in that country. This research was carried out to examine the influence of Country-of-Origin (COO) information on Chinese and British customers buying behaviours and how they perceive the quality of products made in specific countries. The findings are aimed to assist international marketing manager to realize the different consumer perceptions toward COO information between developed and developing countries, and consequently establish more efficient marketing strategies to Chinese market.